Microverdes de coentro com iluminação artificial: rendimento, eficiência energética, concentração mineral e atributos sensoriais - Viana, Caris dos Santos (2023)
Microgreens are vegetables harvested from 7 to 21 days after sowing (DAS), in controlled environment conditions, under light emitting diode (LED) lighting. Coriander is a vegetable cultivated as a microgreen, whose cultivation conditions are not well established. Thus, the objective was to develop an artificial lighting protocol that allows the production of coriander microgreens with better biometric aspects, yield, energy efficiency, concentration of mineral nutrients and consumer acceptance. For that, experiments were carried out in the laboratory of Olericulture of the Department of Phytotechnics of the Federal University of Ceará-UFC, Campus do Pici and were maintained in a growth room with a controlled environment, the temperature set at 20 ± 2°C and relative humidity between 60- 70%. Microgreens of coriander cultivar 'Verdão' (TopSeed®) were produced in polypropylene trays, filled with coconut powder substrate and vermiculite in the proportion of 5:1 (v/v) and irrigated by sub-irrigation with nutrient solution. In all experiments, the light quality factor was kept fixed, which consisted of white light as a control and three other proportions of red and blue light, , “R” and “B”, along the LED strip, being 3R:1B; 4R:1B and 5R:1B. The quality of light and the distribution of LED strips (2 and 3 LED strips) on the luminous panels were evaluated, as well as the quality of light at three different exposure times (from the moment of sowing; 2 and 4 DAS). We evaluated the quality of light and the luminous intensity generated at different distances between the surface of the substrate and the light source (30, 40 and 50 cm), three photoperiods: 16 hours of light/08 hours of dark (08/16); 12 hours light/12 hours dark (12/12) and two cycles of 8 hours light/4 hours dark (04/08-2x) combined with the same light qualities as in previous experiments. Finally, biometric, performance and energy efficiency evaluations were carried out, as well as evaluations of the quality of light within the conditions determined as the most appropriate in each experiment conducted. Biometric, yield, nutritional, sensory and consumer acceptability analyzes were carried out. The results showed that three LED strips on the light panels improved the intensity and spatial distribution of light. Exposure to 2 and 4 DAS enabled greater efficiency in the use of energy and greater yield of microgreens. The distance of 30 cm from the light source to the surface of the substrate improved the spatial distribution and increased the light intensity and yield of the microgreens. Photoperiods 08/16 and 04/08 (2x) allowed higher yield. In all experiments, red and blue lighting provided higher yields than white lighting. The R:B lighting, with a higher proportion of blue light, provided a higher concentration of chlorophyll a and carotenoids. The highest concentration of mineral nutrients varied among the microgreens, with the highest mineral density being in the microgreens grown under R:B lighting, which had the highest percentages of dry matter. In the sensory analysis, the attributes of color, appearance, aroma, texture, flavor and global acceptance did not differ, and the samples were classified between “liked” and “liked a lot”, indicating good acceptability by consumers. The R5:B1 ratio, with three LED strips distributed on the luminous panel at a distance of 30 cm from the surface of the substrate, with lighting starting 4 days after sowing, in a photoperiod of 16 hours of continuous light or in 2 cycles, provides greater yields, high concentrations of mineral nutrients and good consumer acceptance. The cultivation of coriander microgreens under white light allows a higher yield per amount of input energy, being a way to reduce costs in its production.